Biocompatible formulations based on mycosynthesized iron oxide nanoparticles: Fabrication, characterization, and biological investigation. (18th December 2022) - Kamal, Asif; Saba, Malka; Farooq, Muhammad
Abstract: The current study was carried out to synthesize iron oxide nanoparticles (IONPs) via green reduction method from a wild mushroom collected from Quaid‐i‐Azam University, Islamabad, Pakistan. The collected fungus was identified as Daedalea sp. based on morphological characteristics. Prepared NPs were produced from iron chloride hexahydrate with fungal filtrate via combustion method. The as prepared NPs were characterized by using different techniques for example, scanning electron microscopy (SEM), X‐ray diffractions (XRD), Fourier transform infrared spectroscopy (FT‐IR), and ultraviolet visible (UV‐Vis) spectroscopy. Morphology and size of the NPs were determined by SEM analysis. XRD study revealed crystalline nature of IONPs. The FT‐IR spectrum exhibited peak at 3390.26 cm − 1 stretching that described the strong O–H band of the alcohol associated with mushroom texture. The major IONPs dose (0.75 mg/ml) demonstrated 71% growth inhibition against Aspergillus. Excellent antibacterial activities against Pseudomonas aeruginosa (28 mm), and Klesbsilla pneumonia (28 mm) were represented by the fabricated NPs. Further, highest reducing power (53.22 ± 0.72 µg AAE/mg) was shown by the highest administrated dose (400 µg/ml). Maximum 2, 2‐diphenyl‐1‐picrylhydrazyl and trolox antioxidant activity free radical scavenging activities at 400 µg/ml IONPs concentration were noted as 51.29 ± 0.48, and 83.12 ± 0.28 trolox equivalent antioxidant capacity, respectively. In brief, the negligible hemolytic activity against human red blood cells at the highest concentration (400 µg/ml), as well as, moderate antioxidant activities at low concentration suggest the application of the fabricated NPs in environmentally sound viable hygiene production.